Pengetahuan, Sikap Dan Personal Hygiene Tenaga Penjamah Makanan Di Ruang Pengolahan Makanan - Amalia Safitri Assidiq; Made Darawati; AASP Chandradewi; Ni Luh Suranadi (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background. According to Fatmawati, et al. (2013), one of the basic principles of organizing institutional food is the organization of foods that implement hygiene and sanitation in accordance with applicable regulations. One of the factors that support the principle of hygiene and sanitation in the provision of food is the factor of personal food hand hygiene. Personal hygiene is a clean, safe and healthy behavior of food handlers to prevent food contamination from food preparation to food serving. Some important procedures for food handlers, namely washing hands before and after handling food, using complete personal protective equipment and personal hygiene and health. This study aims to determine the description of knowledge, attitudes and personal hygiene of food handlers in the food processing room of the Tabanan General Hospital. Research Methods. This type of research is observational descriptive and in terms of time, including the type of cross-sectional study. Data collection methods used were questionnaire and observation. Research Result. The sample used was all food processing staff at the Nutrition Installation of the Tabanan General Hospital as many as 14 people. Most of the food processing staff were female (64%), were in the age range between 30-49 years (79%), the last education was secondary education (86%) and had worked for more than 3 years (100%). The average overall knowledge, attitude and application of personal hygiene of food handlers are included in both categories. Knowledge and attitudes of all food processing staff are included in the good category because ISO 9001: 2015 has been applied. Likewise, the application of personal hygiene before and after ISO 9001: 2015 shows that all food processing personnel apply personal hygiene well.